History of the Polish Dermatological Society - Lidia Rudnicka (Przegląd Dermatologiczny, 2023)
The Polish Dermatological Society was founded in February 1920 by Franciszek Krzyształowicz (1868–1931), Robert Bernhardt (1874–1950), Roman Leszczyński (1873–1940), Jan Lenartowicz (1877–1959) and Franciszek Walter (1885–1950). For 100 years of the existence of the Polish Dermatological Society, the most important goal was to build cooperation and the best possible, science-based, quality of dermatology in Poland, as well as building a favorable image of Polish dermatology and Polish dermatologists in the world. The Society now has over 2,600 members, the most in the history of our Society. The Polish Dermatological Society, was created by people with a passion for dermatology and cooperation. Now, after it was developed by several generations dermatologists we can look with optimism into the next 100 years.